Neoadjuvant therapy for HER2-positive breast cancer - Dragana Jokanović; Slađana Popović; Olivera Čančar; Nikolina Dukić; Zdenka Gojković; Nenad Lalović; Jelena Vladičić Mašić; Srdjan Mašić (Биомедицинска истраживања, 2019)
The human epidermal growth receptor 2 (HER2, c-erb-B2) is present in 15-20% of breast cancer at the time of diagnosis. Overexpression of HER2 receptor is associated with more aggressive form of breast cancer. Trastuzumab is a human monoclonal antibody that blocks the signaling pathways of cell proliferation by binding to the HER2 receptor. Due to the possible occurrence of resistance to trastuzumab (binds to the subdomain of II HER2 receptor and thus achieves the ligand-independent inhibition of cell proliferation), another monoclonal antibody pertuzumab was produces in the course of time (binds to the subdomain of IV HER2 receptor and thus achieves the ligand-dependent inhibition of cell proliferation), forming the basis of dual HER2 receptor blockade. Numerous studies have shown the benefits of administering trastuzumab and pertuzumab, initially in metastatic, and then in adjuvant and neoadjuvant regimens. Neoadjuvant (preoperative) therapy is given in inoperable tumors, in patients at high risk of poor outcomes (HER2-positive tumors, nodus positive tumors, inflammatory breast cancer, large tumors), as well as in additional risk factors - HR negative tumors where no beneficial effect is expected from the hormonal therapy in the adjuvant setting. Neoadjuvant therapy also provides an "in vivo" insight into the tumor response to neoadjuvant therapy. A pathological complete response (pCR) is an early parameter of the effectiveness of neoadjuvant therapy which also allows us to discover the sensitivity of the tumor in time and make a decision on adjuvant treatment. pCR has a predictive and prognostic value. Namely, the rate of pCR is associated with desease-free survival and overall survival. On the basis of the rate of pCR, numerous studies have shown that there are subgroups of HER2-positive breast cancer: subgroup of hormone receptor-negative tumors that have a higher response rate to the existing anti-HER2 therapy and HER2-positive breast carcer; the subgroup of hormone-dependent tumors in which an adequate pCR rate is not achieved by existing therapeutic options, which represents a new area of research and the possibility for finding new treatment strategies.
Keywords: breast carcer; HER2 receptor; neoadjuvant therapy; pCR; trastuzumab; pertuzumab